O comportamento da demanda e suas implicações na gestão de operações: um estudo de caso de uma empresa de eletrodomésticos. - Soares, Hugo Freneda (2006)
The high competitiveness imposed by the current market characterized by the global competition and by consumer requirements, have been causing more complexity in the enterprise management. Because of that, the increase in the diversity of products offered to the market, and the availability of these products at the precise time and number, have become important competitive plus. We can add to these factors others previously existent, as price and quality, equally important. The forecasting management is the determinant function to this environment, in order to achieve the required availability, with cost efficiency. This function consists of the historical data explains and the consumers future behavior. The areas more directly connected to forecasting management are: (a) Marketing, (b) Production Control Planning, (c) Manufacturing, (d) Material Control Planning, (e) Logistic, (f) Supply Chain. In this way, observing the current enterprise difficulties, this research has the goal to analyze in details the forecasting management matter, an then identify better operations management practices. In order to better feature the issue, a case study has been carried out at a white goods company in Brazil. The case study acknowledged the importance of forecasting for operations. Furthermore, good practices have been identified to help the production manager work.